Sea fish industry in 2014. - Szostak, Stanisław; Rakowski, Marcin; Budny, Teresa (Morski Instytut Rybacki - PIB, 2015)
The report is presented every year and shows statistics data on Polish fish industry. It contains not only the description of the industry but also many tables on fisheries fleet, catches, caught species, geographic regions of fisheries, fish consumption etc. Published